If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 9rtx + -5 = 0 Reorder the terms: -5 + 9rtx + 2x = 0 Solving -5 + 9rtx + 2x = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 9rtx + 5 + 2x = 0 + 5 Reorder the terms: -5 + 5 + 9rtx + 2x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 9rtx + 2x = 0 + 5 9rtx + 2x = 0 + 5 Combine like terms: 0 + 5 = 5 9rtx + 2x = 5 Add '-2x' to each side of the equation. 9rtx + 2x + -2x = 5 + -2x Combine like terms: 2x + -2x = 0 9rtx + 0 = 5 + -2x 9rtx = 5 + -2x Divide each side by '9tx'. r = 0.5555555556t-1x-1 + -0.2222222222t-1 Simplifying r = 0.5555555556t-1x-1 + -0.2222222222t-1 Reorder the terms: r = -0.2222222222t-1 + 0.5555555556t-1x-1
| x^2+20x+7=0 | | 3(x+2)=x+(x+2)+(3x-1) | | X+X=(30*3*2) | | -6-3(2k+4)=-8 | | 4(2x-3)=-5 | | 3x(2x-3)=0 | | 6x^2+4x-54=0 | | 4x+6x=10x | | p+p+p+p= | | 19=3x | | X(4X+5)-3=0 | | X(4X+5)-3=5 | | 4(-4t^2+27-45)=0 | | 5x-3=-1 | | 9x^2+60x+100=0 | | 6(3-a)+7(3a+2)-4(a+5)= | | 9x-5x+8x-6x= | | (2+y)+y=4 | | 15-13x-20x^2=0 | | -X+2y=1 | | 5+(2-3)-(6-4)+7= | | 2x-10=48 | | 14+(-3)-(-6)+8= | | 7(2)+7y=-10 | | 72+7y=-10 | | X+(2+X)=4 | | 54+68=158 | | 6(k-2)-7=3k-(2k-3) | | 6w^2-4w^3= | | 1/2(6x+4)=x+2(x+1) | | 2(x+1)=8-x | | 4a-5=2(a+1)+9a+2 |